From agrochemicals to thyroiditis: The alarming connection with neonicotinoid insecticides - Jingxia Li; Yanfang Chen; Shunyan Kan; Guang Yang; Shuai Yang; Taoping Sun; Hua Zhang (Environmental Chemistry and Ecotoxicology)
Neonicotinoid insecticides (NEOs) are among the most widely used agrochemicals globally, yet their potential impacts on human thyroid health remain poorly understood. Here, we investigate the association between NEO exposure and thyroiditis in a South Chinese cohort (n = 754), comprising 298 healthy controls and 456 thyroiditis patients. Blood samples were analyzed to quantify the concentrations of 8 NEOs and 4 metabolites. Our findings revealed a high detection frequency (67 %–100 %) of the target analytes in both cohorts. Dinotefuran (DIN) emerged as the predominant NEO, accounted for 43 % of healthy individuals and 64 % of thyroiditis patients. Notably, the thyroiditis cohort exhibited significantly elevated concentrations (p < 0.05) of most target analytes compared to the healthy cohort, suggesting heightened exposure to NEOs among thyroiditis patients. Logistic regression demonstrated a dose-dependent relationship between NEO levels and thyroiditis (p < 0.05), implying that these pollutants may elevate the risk of thyroiditis development. Furthermore, multilinear regression identified significant associations (p < 0.05) between specific NEOs (i.e., DIN, acetamiprid, imidacloprid, thiamethoxam, nitenpyram, 5-hydroxy-imidacloprid, and N-desmethyl-acetamiprid) and altered thyroid function markers, including free triiodothyronine (FT3), free thyroxine (FT4), thyroid-stimulating hormone (TSH), and thyroglobulin antibody (TgAb), implicating NEOs in thyroid dysregulation. Our study provides the first epidemiological evidence linking NEO exposure to thyroiditis, highlighting a potential endocrine-disrupting mechanism. Given the widespread use of NEOs, these findings underscore the need for further toxicological evaluation and regulatory scrutiny to mitigate potential public health risks.